THE RELATIONSHIP BETWEEN SERVICE DEVELOPMENT AND ECONOMIC LIBERALIZATION (ON THE EXAMPLE OF BANKING SERVICES) (Journal of Economic Research & Business Administration, 2018)
This work is devoted to liberalization in the sphere of banking services; the study has been carriedout to identify the relationship between liberalization and the development of the banking services sector.The works of foreign and domestic scientists on liberalization of services, liberalization of bankingservices and the development of banking services were studied to explore the influence of liberalizationon increasing the availability and reliability of banking services. The scientific significance of this study isan identification of the relationship between liberalization and indicators of reliability and accessibility ofbanking services. The data obtained during the research can be applied in the deregulation of the sphereof production of services, particularly in banking, and these studies can be used to prepare policies forthe development of the services sector. The study used structural-logical analysis to construct logicalrelationships, as well as empirical analysis to determine the degree of liberalization of banking services inKazakhstan. Based on the data of rating agencies, the current state of the banking sector of the Republicof Kazakhstan was analyzed on the reliability parameter. The analysis of the impact of such liberalizationprocesses as providing a free currency regime, liberalizing currency operations, eliminating restrictionsfor foreign banks, and softening requirements for licensing on the reliability and accessibility of bankingservices was conducted during this research.